THE OPTIMIZATION OF REINFORCING STEEL BY IRON FIBER (LATHE WASTE) AND OFFSET TECHNIQUE AT THREE-DIMENSIONAL PORTAL - Samuel Layang; Wiratno (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2015)
The objective of this study is to determine the effect of metal fibres (lathe waste) usages and offset technique at three-dimensional portals to the reinforcement wide. The study was conducting by experimental in laboratory. This experiment is arranged by testing of 25 cylindrical concretes (size 15 cm x 30 cm) under mix design method of SNI 03-2834-2000 (The procedure of making a normal concrete mix plan). All concrete cylinders were tested at 28 days of age in order to obtain an actual compressive strength. The ultimate moment capacity of three-dimensional portal is analyzed by STAAD Pro 2004 engineering computer program. The results of test shows that the compressive strength on concrete with 8% steel fibres is increased up to 45.46%. And the reinforcement wide were decresing up to 1.87% (pedestal level 1); 2.95% (pedestal level 2); 2.67% (field level 1) and 3.99% (field level 2). The beams which only using the offset technique will save the use of steel amounted to 17.81% (pedestal level 1); 18.25% (pedestal level 2); 2.38% (field level 1) and 2.80% (field level 2). Beams that used iron fibres and the offset technique will save the use of steel amounted to 18.25% (pedestal level 1); 20.18% (pedestal level 2); 4.92% (field level 1) and 6.55% (field level 2). Its decresing wide was showing on statics analisys and caculation of reforcing steel requirement.